DISTRIBUSI VERTIKAL DAN HORIZONTAL Asplenium nidus L. DI TAMAN NASIONAL GUNUNG HALIMUN, JAWA BARAT - Muhammad Mansur; Takashi Kohyama; Herwint Simbolon; Tukirin Partomihardjo; Tomokazu Tani (BERITA BIOLOGI, 2004)
The study was carried out on August 2000 to July 2001, in 1-ha permanent plot, near Cikaniki Research Station, in Halimun Mountain National Park, West Java.The results shows that, from 1 ha (100 sub plots, each 10x10 m size) studied there were 388 individual numbers of Asplenium nidus L. with some variation on rosette leaves size. The individual numbers of A. nidus were greater at host plant stem with diameter class distribution between 1.3-9.9 cm (45,6%), and than percentages value were decreased in the larger of host plant stem diameter class. Also the individual numbers of A. nidus were greater at under 5 m height position above ground, that is 252 (65,1%).There were no correlation between host plant height (tree trunk height) and A. nidus height position above ground.However there were little linear correlation between rosette leaves size with stem diameter of host plant(Y=1.5586x+317.37 and R =0.0211), and little linear correlation between rosette leaves size with host plant height(Y=2.8241x+304.63, and R =0.0226), but there were no significant increased for both. It was assumed the effects of microclimate(temperature, humidity, light, and rainfall) to distribution of A. nidus as well as horizontal or vertical distribution.